The theoretical insights of the state’s promotion policy on FDI - Romualdas Ginevičius; Agnė Šimelytė (Business: Theory and Practice, 2011)
This article critically examines the concepts of public policy in respect of foreign direct investment. The analysis of the concepts of public policy identifies two main theoretical approaches to the promotion of foreign direct investment, namely – the liberal, and the regulatory one. A regulatory policy is a matter of fierce dispute, which in some cases creates a negative perception of a country. Thus, the intensity of investment of a host country is declined. This article also introduces some specific attitudes towards the intervention of a state. A liberal government policy on foreign direct investment is widely applied all over the world. However, nowadays more and more countries tend to switch from the liberal government policy to the regulatory one. Therefore, this article discusses the main causes of this phenomenon. The benefit of the regulatory policy towards FDI is emphasized.